2005
DOI: 10.1158/1078-0432.ccr-05-0844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Antitumor Efficacy of Doxorubicin in MDA-MB-231 Breast Cancer Xenografts

Abstract: Purpose: Exercise is becoming readily accepted as a beneficial adjunct therapy to maintain or enhance quality of life in breast cancer patients undergoing adjuvant chemotherapy. An essential precursor to these studies is to investigate whether exercise modulates the antitumor efficacy of chemotherapeutic agents. Experimental Design: Athymic female mice were transplanted with MDA-MB-231 breast xenografts and randomly assigned to one of four groups (n = 21 per group): (a) control, (b) exercise-only, (c) doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 24 publications
0
43
1
2
Order By: Relevance
“…However, the tumors' weight and volume were higher in MNU exercised animals, which is not in accordance with the results previously described by Whittal-Strange et al [32]. As the animals of this experiment were exercised during a longer period, these different results may be associated with the improvement of mammary tumors blood perfusion induced by exercise training [18]. It was observed that the VEGF-A expression and the mean number of microvessels were higher in exercised animals [37].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, the tumors' weight and volume were higher in MNU exercised animals, which is not in accordance with the results previously described by Whittal-Strange et al [32]. As the animals of this experiment were exercised during a longer period, these different results may be associated with the improvement of mammary tumors blood perfusion induced by exercise training [18]. It was observed that the VEGF-A expression and the mean number of microvessels were higher in exercised animals [37].…”
Section: Discussioncontrasting
confidence: 70%
“…Among the potential anticancer effects of physical activity are the decrease in endogenous sex hormone concentrations and exposure (later age of menarche, decreased estrogen concentrations, decreased number of ovulatory cycles), favorable changes in body weight, insulin resistance, up-regulation in immune system and chronic low-grade inflammation [1,[17][18][19][20][21]. However, there is a need for consistent molecular evidences of the putative preventive effect of exercise training programs to allow the public to better understand the benefits of an active lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the application of exercise to improve the therapeutic index of these treatments (i.e., a therapy sensitizer) may also be plausible. In an initial study, we found that tumor growth (survival) was comparable between mice bearing human breast cancer xenografts receiving exercise in combination with doxorubicin (a common chemotherapeutic agent) or doxorubicin alone (22). Although these results do not support our hypothesis, this study had several cautionary limitations (e.g., use of forced exercise, subcutaneous tumor implantation, no tumor histological analysis) and is by no means conclusive.…”
Section: Discussionmentioning
confidence: 68%
“…Because exercise is clinically recommended at all points following cancer diagnosis, it is important to investigate the effects of exercise on a clinically relevant dose of DOX. One previous study showed that exercise did not impact tumor burden at a 32 mg/kg cumulative dose of DOX over 8 wk (21). At suprapharmacologic levels, DOX efficacy may be saturated.…”
Section: Discussionmentioning
confidence: 96%